2020
DOI: 10.1186/s13213-020-01550-3
|View full text |Cite
|
Sign up to set email alerts
|

Selected bacterial strains enhance phosphorus availability from biochar-based rock phosphate fertilizer

Abstract: Purpose The co-pyrolysis of biomass and soluble phosphates generates biochar-based phosphate fertilizers (BBF), which may enhance phosphorus (P) input in soil and P uptake by plants. Conversely, pyrolysis of biomass impregnated with rock phosphate results in low P solubility and may not supplement plant requirement in short term. However, bacterial strains promoting rock phosphate solubilization increases P use efficiency and can be applied to BBFs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Vitron) were surface sterilized using 98% ethanol (30 s) and 2% sodium hypochlorite (2 min) and successively washed with distilled water. Then, 20 seeds of wheat were placed in sterile Petri dishes (100 mm × 15 mm) containing agar media (0.8% of agar) and inoculated with 48 h of each actinobacterial culture (1 mL) containing 10 8 UFC/mL [37]. The plates were incubated at 28 • C for 11 days.…”
Section: Effect Of Actinobacteria Strains On Wheat Germination: In-vitro Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitron) were surface sterilized using 98% ethanol (30 s) and 2% sodium hypochlorite (2 min) and successively washed with distilled water. Then, 20 seeds of wheat were placed in sterile Petri dishes (100 mm × 15 mm) containing agar media (0.8% of agar) and inoculated with 48 h of each actinobacterial culture (1 mL) containing 10 8 UFC/mL [37]. The plates were incubated at 28 • C for 11 days.…”
Section: Effect Of Actinobacteria Strains On Wheat Germination: In-vitro Testsmentioning
confidence: 99%
“…Wheat (Triticum aestivum variety Vitron) was grown in PVC pots (150 mm height, 80 mm diameter) containing 1.5 kg of sterilized mixture of sand (with low P) and perlite (3:1 w/w). Before sowing, seeds were first surface sterilized with 2% (v/v) sodium hypochlorite for 1 min, 95% (v/v) ethanol for 30 s, and then washed with sterile distilled water for 1 min (three times) [37]. Pots (four seeds per pot) were arranged according to a completely randomized block design with five replicates and six treatments: (1) (C−) negative control (without bacterial inoculation, Mica, nor RP fertilization); ( 2 Microbial inoculation was performed by adding 2 mL of each Actinobacteria suspension (OD = 1) in the vicinity of the root zone.…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
“…Kocsis et al (2020) also reported that appropriate biochar doses are needed for the improvement of soil biological activities and increased yield of maize compared to the control. In addition, bacterial inoculation in biochar-based rock phosphate enhanced available P in soil (de Amaral Leite et al, 2020). Mycorrhizae colonization was significantly decreased fertilizer input by 100 mg P kg −1 ; and a combination of mycorrhizae fungi, biochar and P fertilizer significantly increased shoot biomass in polluted soils and the growth of chili in sandy soil (Putra et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that application of fertilizer phosphorus (rock phosphate or single super phosphate) increased productivity and biomass production of corn and groundnut over no fertilizer application (Kamara et al, 2011;Cong, 2017). The solubilization of rock phosphate is associated with release of organic acids that decreases the pH, chelates the cations bounded to phosphate, thereby leading to an increased solubility of mineral phosphates (De Amaral Leite et al, 2020;Nacoon et al, 2020).…”
Section: Statistical Analysesmentioning
confidence: 99%